Studying the Effect of Different Vortex Generator Geometries and Arrangements on Heat Transfer Performance of Heat Sinks - Mohsen Motahari-Nezhad; Shayan Fathi; Mohammad Eftekhari; Armen Adamian (International Journal of Advanced Design and Manufacturing Technology, 2020)
In this paper, different geometries and arrangements of vortex generators for improving the heat transfer performance of heat sinks have been studied. The effect of different parameters including the inclination angle of vortex generators and the distance between them are also investigated on heat transfer performance of heat sinks. Numerical computations are done based on the finite volume method and they have been validated with available experimental data which were in accurate compatible with each other with RMSE error of less than 6%. According to the obtained outcomes, between rectangular, triangular and symmetrical NACA0012 vortex generator, heat sink with NACA0012 vortex generator has the best thermal performance. On the other hand, heat sink with rectangular vortex generator has the highest fluid flow pressure drop. So, using rectangular vortex generator with heat sink needs a fan with the highest power. Also, the results show that thermal resistance of the heat sink decreases with Reynolds number increase. Also, heat sink pressure drop increases with Re number enhancement. Meanwhile, the pressure drop rate is more sensible in higher Reynolds numbers.